Metal-free super-wideband THz absorber for electromagnetic shielding. (9th December 2021) - Soni, Anil Kumar; Giri, Pushpa; Varshney, Gaurav
Abstract: A technique is implemented for obtaining the high absorption over super-wideband (SWB) in a metal-free THz absorber. The multiple resonant modes with wide spectra are generated in a graphite-based resonator placed on a dielectric cavity merging of which provides the SWB response. The low permittivity dielectric slab sandwiched between the graphite sheet at its bottom and graphite resonator at its top acts as the Fabry–Perot cavity where absorption takes place. The high absorption rate of graphite in the THz regime can make it a suitable candidate for its utilization in implementing the broadband absorber. Thus, the molecular transition due to interaction of energy in graphite also provides the high absorption. The absorption bandwidth can further be enhanced by stacking of multiple layers in two different configurations of the proposed unit cell. The absorber maintains the polarization insensitivity due to symmetry and allows the high absorption for the electromagnetic wave incident up to the angle of more than 75 ° . The proposed absorber can be utilized in the THz electromagnetic shielding applications due to its SWB response.